Ingenious [videorecording (DVD)] - Renner, Jeremy; Roberts, Dallas; Zorer, Ayelet (2013)
Lifelong friends Matt and Sam are searching for the one big idea that will change their lives forever. But their inventions fall flat and their sales techniques leave the customers wanting. In need of cash, they turn to Matt's girlfriend Gina. When one bad decision costs them everything they have and puts their friendship to the test, they find that hitting rock bottom could lead them to the most ingenious idea they've ever had.